LED light assembly having axially coupled LED light modules - Huynh, Patrick; Steedly, James (2019)
In a first aspect of the subject invention, an LED light assembly is provided comprising: a housing; and, a plurality of LED light modules coupled together in axial end-to-end fashion so as to define an elongated lighting strip, each said light module including at least one heat dissipation block and at least one LED element, wherein, said lighting strip is secured to said housing.